The community museum: a space for the exercise of communal power (Cadernos de Sociomuseologia, 2010)
This paper discusses two key elements in the field of museums: a summary of the concept of the community museum, on the one hand, and, on the other, a proposal as to how this concept is put into practice, especially in the early stages of the creation of the museum, when the social basis for the project is being established. We will discuss how the community museum combines and integrates complex processes aimed at strengthening the community as a collective subject, asserting its identity, improving its quality of life and building alliances between communities. In the second part, which has a methodological focus, we will discuss how the museum is born out of community aspirations to strengthen its identity and integrity, the initial process of consensus-building, the roles of different agents, both internal and external to the community, as well as some factors that foster or prevent community appropriation. To conclude we will emphasize the potential of community museum networks as a strategy to generate a broader field of action, in which communities can exercise greater autonomy, by collectively developing and appropriating projects of regional and even international scope.